Effects of APOE ε2 on the Fractional Amplitude of Low-Frequency Fluctuation in Mild Cognitive Impairment: A Study Based on the Resting-State Functional MRI - Liu, Xiaocao; Zeng, Qingze; Luo, Xiao; Li, Kaicheng; Hong, Hui; Wang, Shuyue; Guan, Xiaojun; Wu, Jingjing; Zhang, Ruiting; Zhang, Tianyi; Li, Zheyu; Fu, Yanv; et al. (Frontiers in Aging Neuroscience, 2021)
Background: The apolipoprotein E (APOE) ε2 is a protective genetic factor for Alzheimer's disease (AD). However, the potential interaction effects between APOE ε2 allele and disease status on intrinsic brain activity are still unclear. Method: We identified 73 healthy control (HC) with APOE ε3/ε3,61 mild cognitive impairment (MCI) with APOE ε3/ε3, 24 HC with APOE ε2/ε3 and 10 MCI with APOE ε2/ε3 from the ADNI database. Subjects underwent resting-state functional MRI and FDG-PET. To explore the spontaneous brain activity, we used the established metrics fractional amplitude of low-frequency fluctuation (fAlff). Based on the linear mixed model, we investigated the interaction effects of APOE ε2 allele and disease status on brain activity and metabolism in a voxel-wise way (GRF corrected, p < 0.01), followed by post hoc two-sample t-tests (Bonferroni corrected, p < 0.05). We then extracted and correlated the mean imaging metrics with cognitive abilities. Results: No significant differences were found in terms of gender, age, or education among the four groups. The interaction effect on brain activity was located in the inferior parietal lobule (IPL). Post hoc analyses found that APOE ε2/ε3 MCI had decreased IPL fAlff than APOE ε3/ε3 MCI. Regarding the main effects, APOE ε2 carriers have decreased fAlff in the transverse temporal gyrus than non-carriers. Also, FDG-PET analysis showed lower precuneus fAlff values in APOE ε2 carriers than non-carriers. Further, IPL fAlff negatively correlated with visuospatial function (r = -0.16, p < 0.05). Conclusion: APOE ε2 carriers might have a better brain reservation coping with AD-related pathologies in a compensatory mechanism.